Control of blood pressure and blood glucose levels has important clinical significance to the retina - Jin-Bao Ma; Ming-Zhao Qin; Kai Cao; Yong-Peng Zhang; Cai-Xia Guo (BMC Ophthalmology)
Abstract Background To investigate whether blood pressure and blood glucose levels affect retinal microvascular parameters, reflected by density within 300 μm surrounding the avascular area of the fovea (FAZ), also called FD-300. Methods A case series study design was used to include patients with essential hypertension and/or type 2 diabetes who were hospitalized in the Department of Geriatrics, Beijing Tongren Hospital, from January 2023 to January 2024. FD-300 was measured via optical coherence tomography angiography. Multivariate linear regression analysis was used to adjust for confounding factors and then explore the influencing factors of FD-300. Results Patients were divided into four subgroups according to the quartile of FD-300. The median systolic blood pressure (SBP) levels of the four subgroups were 128 mmHg, 128 mmHg, 126 mmHg, and 121 mmHg, respectively, which were significantly different (p = 0.046). The median glycated hemoglobin (HbA1C) levels of the four subgroups were 6.50%, 6.40%, 6.50%, and 6.00%, respectively, which were significantly different (p = 0.012). Spearman correlation analysis revealed a significant negative correlation between SBP and FD-300 (r= -0.183, p < 0.05) and between HbA1c and FD-300 (r= -0.207, p < 0.05). Age, disease duration, cystatin C, and low-density lipoprotein cholesterol were also correlated with FD-300; they were confounding factors and were adjusted by multivariable linear regression. The results revealed that both SBP (β=-0.07, p = 0.005) and HbA1c (β=-1.00, p < 0.001) had significant effects on FD-300. Conclusion High blood pressure and glucose levels are risk factors for FD-300. Good control of blood pressure and glucose is of clinical importance for preventing retinal microangiopathy. Registration NCT05644548 (clinicaltrials.gov).Registration Date: 2022.12.09.